Blood biochemical values of does and kids in the semi-arid Region of Brazil - Unanian, Maria Marina; Silva, Antonio Emidio D. Feliciano (Pesquisa Agropecuaria Brasileira, 2014)
This research was carried out at the Centro Nacional de Pesquisa de Caprinos in Sobral, CE, Brazil, with the objective of determining normal biochemical values in the blood serum of local goats, mantained in nativo caatinga. The concentration of total protein, albumin, total globulin, glucose, magnesium and coppor was estimated in the blood serum of 43 does from different breeds and their 62 kids born from 19 twin and 24 single pregnancies. The blood biochemical values were analysed at parturition and during lactation (FF), until 45 days after parturition and in relation to type of pregnancy (TP) and sex (Sx) of kids. All the blood parameters of the does and kids were influenced by physiological states (FF) (parturition and lactation (P < 0.01). No one biochemical level in the does blood varied with type of pregnancy (P> 0.05). Also in the does blood a variation of the albumin and of total globulin values with FF x TP interaction was observed. Some of lhe kids parameters were influenced by sex and type of pregnancy such as albumin (P < 0.01 and P < 0.05) and magnesium by the sex (P < 0.05). The interaction TP x FF and Sx x FF were also significant for the albumin (P < 0.01) and magnesium (P C 0.01). The knowledge of this values may help to establish nutritional deficiencies, during lactation, and management with special regards to the supplementations.